Pelatihan Deteksi Dini Tumbuh Kembang Anak Bagi Guru Tk/Ra Se-Kota Kendari - Salwiah; Abubakar, Sitti Rahmaniar; Saranani, Muhamad Safiuddin; Asmuddin; Hidayat, Ahid; Gadafi, Muamal; Hidayah, Afifah Nur; Mustar, Sri Yuliani (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
This Community Service Program is entitled